Estudos espectroscópicos de novos complexos B-dicetonatos de íons lantanídeos com emissão no visível e infravermelho próximo - Moura, Jandeilson de Lima (2017)
This work reports the synthesis, characterization and investigation of the luminescent properties of new lanthanide -diketonate complexes, Ln(- dic)2(NO3)L2, Ln(TTA)3L2 and Ln(DBM)3L (TPPO), where thenoyltrifluoroacetone (TTA) and dibenzoylmethane (DBM), L = triphenylphosphine oxide (TPPO), tributylphosphine oxide (TBPO), and trioctylphosphine oxide (TOPO). Eu3+ ion complexes were also synthesized with triphenylarsine oxide (TPAsO) and tricyclohexylphosphine (TCHPO) as auxiliary ligands. The complexes were characterized by complexometric titration with EDTA, CHN elemental analysis, Fourier transform infrared (FTIR) absorption spectroscopy and thermogravimetric analysis (TGA). The photoluminescent properties in the visible and near infrared (NIR) regions of the synthesized complexes were investigated from excitation, emission and luminescence decay curves. The excitation spectra are characterized by the presence of large bands associated with transitions centered on the ligands, evidencing the efficiency of the luminescence sensitization by the antenna ligands. The emission spectra in the visible region of the compounds of the Sm3+ and Eu3+ ions show narrow bands attributed to intraconfigurationtransitions and are dominated by the hypersensitive transitions (~645 nm) and (~612 nm). The values of the intensity parameters and for the complexes of Sm3+ and Eu3+ presented a good correlation, evidencing that the chemical environment influence in a similar way the spectroscopic properties of these ions. The photoluminescent properties of the Eu3+ ion complexes were investigated by the intensity parameters and , radiative and nonradiative ( and ), lifetime of the emitting state () and quantum emission efficience . The highest values of are found for Eu(-dic)2(NO3)L2 complexes, in the range of 51-86%. It was observed that the Eu(-dic)3L2 compounds exhibited shorter lifetimes, which may be related to the presence of a suppressor channel, resulting in higher values of . The intensity parameters and vary only slightly when changes occur in the number and nature of the ligands of the first coordination sphere, with parameter being more sensitive to changes in coordination geometry. The emission spectra in the NIR region of the bis- and trisdiketonate complexes of Pr3+, Nd3+, Sm3+, Er3+ and Yb3+ ions present characteristic luminescence. Changes in the nature and number of ligands coordinated to the Ln3+ ion slightly influence the spectral profiles. The results obtained for the studied systems suggest that these are potential candidates to act as Molecular Light Converting Devices.